An Exploring Teachers’ Strategy in Assessing Students’ Speaking Performance Based on The Independent Curriculum - Moh.Rozak, Rozak; Abu Na’im Rohman; Junaidi Mistar (Ethical Lingua: Journal of Language Teaching and Literature, 2024)
Abstract The Independent Curriculum was introduced by the Indonesian government to improve the quality of education, address global challenges, and equip students with the necessary competencies and skills to succeed in an increasingly competitive world. This curriculum is expected to lead Indonesian education towards a brighter future in the face of intensified global competition. This study aims to explore the implementation of speaking assessment and its connection to other elements. The research uses a qualitative approach with descriptive design. A questionnaire was used to generate data from respondents of random sampling by sharing a questionnaire through a google form. The researcher used a descriptive design to collect data from 35 English teachers from various cities in East Java. The results showed that teachers demonstrated a strong commitment to implementing speaking assessments by incorporating assessment items into their teaching modules or lesson plans. The most common approach employed by the teachers was having students engage in conversations with one another, facilitated by the teacher who provided topics for discussion. The majority of respondents (97.1%) indicated that they planned assessments, including speaking skills, in their teaching plans. All teachers who have implemented Independent Curriculum carried out pre-test as a diagnostic assessment, aligning with the principles of Independent Curriculum. The findings also shed light on the strategy employed by teachers for speaking assessments. Keywords Teachers’ strategy Speaking assesment Independent curriculum